Study of pharmacokinetic parameters and safety of the drug Duonica® in comparison with the original combination of doxylamine and pyridoxine under fed conditions - I. E. Shohin; S. M. Noskov; A. A. Globenko; N. S. Bagaeva; K. K. Karnakova; O. M. Parulya; L. N. Lutskova; A. V. Kapashin; M. A. Pasko (Фармакокинетика и Фармакодинамика, 2024)
Aim. A comparative study of the pharmacokinetics and safety of the investigational drug Duonica®, enteric-soluble, film-coated tablets, 10 mg + 10 mg (Valenta Pharm JSC, Russia) and the reference drug Diclectin®, delayed-release tablets, 10 mg + 10 mg (Duchesnay Inc, Canada) was conducted as part of the bioequivalence study in healthy volunteers under fed conditions.Material and methods. An open-label randomized crossover two-period bioequivalence study was conducted with 28 Caucasian female volunteers. The study participants were randomly divided into two groups of 14 people depending on the order of drug administration during Periods 1 and 2. Participants randomized to the first group received 2 tablets of Diclectin® during Period 1 and 2 tablets of Duonica® during Period 2. Volunteers from the second group took the study drugs in the reverse order. During each study Period, the drugs were administered after a high-calorie breakfast. The analytes studied were doxylamine and pyridoxal-5-phosphate (an active metabolite of pyridoxine). Methods were developed and validated using high-performance liquid chromatography with a triple quadrupole tandem mass spectrometric detector (HPLC-MS/MS) to quantify the analytes. Pharmacokinetic parameters were calculated from the obtained concentration values and statistical analysis was performed. To confirm bioequivalence, 90 % confidence intervals (CI) for the pharmacokinetic parameters AUC and Cmax of the studied analytes were calculated. The safety of the investigational drugs was assessed based on the frequency, severity and type of adverse events.Results. The 90 % CI values for the ratio of Cmax and AUC(0-t) values for doxylamine were 94.08–113.71 % and 90.63–102.50 %, and for pyridoxal-5-phosphate were 97.34–123.47 % and 90.30–111.03 %, respectively. The obtained CI values were within the limits set by the regulatory requirements and the study protocol (80.00–125.00 %), which allowed us to confirm the bioequivalence of the studied drugs for both components. No adverse events were reported during the study.Conclusion. The study investigated the pharmacokinetics of drugs containing a fixed combination of doxylamine and pyridoxine under fed conditions. The results obtained confirmed the bioequivalence of the drug Duonica® to the reference drug Diclectin®. Both drugs were well tolerated and no differences in the safety profile of the investigational drugs were observed.